Discrimination, Fairness, and the Use of Algorithms. - Holm, Sune Hannibal; Lippert-Rasmussen, Kasper (Res Publica (13564765), 2023)
An introduction is presented in which the author discusses articles within the issue on topics including use of algorithm to discriminate counterfactual condition in decision making, algorithmic discrimination and ethics, and algorithmic fairness criteria in the machine learning community.